A Review of Recent Advancement in Optical Multiplexing Technologies - Ravinshu, Ravinshu; Anjali, Anjali; Pooja, Pooja (International Journal of Computer Sciences and Engineering, 2020)
Optical fiber communication along with the advanced optical networking technologies and advanced modulation formats is an evolving field of research. The enormous bandwidth and long distance reach of optical networks makes them a suitable candidate to be used in backhaul networks. This paper presents a comprehensive review of various advanced optical multiplexing technologies viz: Wavelength Division Multiplexing (WDM), Orthogonal Frequency Division Multiplexing (OFDM), Time Division Multiplexing (TDM) along with several architectural advancements in these optical multiplexing networks is also discussed in a holistic manner.